CzcR-dependent reduction of catalase gene expression and induction of catalase activity in Pseudomonas aeruginosa during zinc excess - Ting Li; Zhifeng Mo; Yuying Zhao; Huiluo Cao; Shuo Sheng; Zeling Xu (BMC Microbiology)
Abstract Background Pseudomonas aeruginosa is able to survive, grow, and cause severe infections at different sites throughout the human body owing to its ability to sense diverse signals and precisely modulate target gene expression using its abundant signaling systems. Release of zinc (Zn) and hydrogen peroxide (H2O2) within the phagocyte are two major host strategies to defend against bacterial infections. It was previously shown that the response regulator CzcR controls global gene expression including catalase genes during Zn excess, but regulatory mechanisms of catalase gene expression and the role of CzcR in H2O2 tolerance remain unclear. Results In the study, comparative transcriptome analysis comprehensively described the CzcR-dependent and -independent gene regulatory pattern in P. aeruginosa during Zn excess, which revealed the counteractive co-regulation of two key H2O2-detoxifying catalase genes katA and katB through CzcR-dependent and -independent pathways in response to Zn excess. Protein-DNA interaction assay demonstrated that CzcR negatively regulates the expression of catalase genes katA and katB by directly binding to their promoters. While interestingly, we further showed that CzcR positively regulates H2O2 tolerance by inducing the catalase activity during Zn excess. Conclusion This study reported the opposite functions of CzcR in negatively regulating the expression of catalase genes katA and katB but in positively regulating the activity of catalase and H2O2 tolerance during Zn excess in P. aeruginosa.